Productivity of Africander, Tswana, Tuli and crossbred beef cattle in Botswana - Trail, J.C.M.; Buck, N.G.; Light, D.E.; Rennie, T.W.; Rutherford, A.S.; Miller, M.; Pratchett, D.; Capper, B. (Cambridge University Press, 1977)
Evaluation of reproductive performance, viability and growth of Afrikander, Tswana, Tuli and crossbred beef cattle in Botswana; data on calving percentage, calf mortality, weaning & birth weights, w. comparison of crossbreeding performance of Tuli, Bonsmara cattle, Brahman cattle & Simmental cattle breeds under dif. management conditions.